Meta-Analysis: Effect of Cigarette Smoke Exposure on Pregnant Women as Passive Smokers on Low Birth Weight - Zonna Aditiya Kusumaningtiyas; Yusuf Ryadi (Masters Program in Public Health, 2022)
Background: Intrauterine exposure to tobacco smoke is considered an important risk factor for low birth weight (LBW) infants, low birth weight (SGA) infants, and preterm delivery. Mothers who smoke during pregnancy are known to limit intrauterine fetal growth and result in low birth weight. This study aims to analyze the effect of exposure to cigarette smoke on pregnant women as active smokers on the incidence of low birth weight.Subjects and Method: This research is a meta-analysis study using PRISMA flowchart guidelines. The article search process was carried out between 2013-2021 using databases from PubMed, Google Scholar and Science Direct PICO, namely, population= pregnant women. Intervention= exposure to cigarette smoke. Comparison= not exposed to cigarette smoke. Outcome= low birth weight. The keywords used for the article search were “Pregnant or pregnancy” AND “smoking” AND “birth weight”. The analysis was carried out using RevMan 5.3 software.Results: There are 8 primary studies spread across 4 continents, namely the continents of Australia, South America, Asia, and Europe, which were selected for a systematic review and meta-analysis. The data found showed that exposure to cigarette smoke in pregnant women as passive smokers increased 2.01 times low birth weight compared to pregnant women who were not exposed to cigarettes (aOR= 2.01; 95% CI= 1.32 to 3.06; p<0.001).Conclusion: Exposure to cigarette smoke in pregnant women as passive smokers increases the risk of low birth weight. Keywords: Low birth weight (LBW), cigarette exposure Correspondence:Zonna Aditiya Kusumaningtiyas. Diploma IV of Midwifery, Health Polytechnics Ministry of Health, Surabaya. Jl. Pucang Jajar Tengah 56, Surabaya, East Java. Email: zonnaaditiya22@gmail.com. Mobile: +62-822-3499-8054.